Analysis of Rake Angle Effect to Stress Distribution on Excavator Bucket Teeth Using Finite Element Method - Suryo, Sumar Hadi; Bayuseno, A. P.; Jamari, J.; Wahyudi, A. Imam (Salehan Institute of Higher Education, 2017)
Excavator is mostly used for mining and construction. This heavy equipment, widely known as a backhoe, is a digging machine commonly used for dredging the mining materials, digging and leveling the soil, dredging the river, removing the road and demolition. Excavator has bucket teeth, component that frequently undergoes a change. The replacement of bucket teeth is performed due to its low usage time and many failure experiences such as wear, bend, crack and facture during the use. To prevent the occurrence of the failures, a structural analysis on bucket teeth is necessarily conducted. The analysis was conducted to find the stress distribution on bucket teeth from the rake angle effect during the excavation. The analysis was performed using finite element method by static loading and two-dimensional modeling to determine digging and resistive force in bucket teeth. Based on the analysis, it was obtained the stress distribution and maximum value of von misses occurring in the bucket teeth from the rake angle effect. The maximum stress, obtained from the analysis results, was then compared to the allowable stress of the bucket teeth material. The results showed that the materials used were in safe limits and had small potential for experiencing failure as well.